Sociological investigation of investment business representatives as potential investors of PAS decentralization project results - Rosha, L. G. (Journal of Education, Health and Sport, 2018)
The purpose is to examine the assessment among the interviewed representatives of the investment business regarding the prospects of the project in the PAS decentralization framework - the creation of a regional pathoanatomical center (RPC)Materials and methods. A specially designed questionnaire interviewed 43 investment business representatives (IBR) as potential investors of the PAS decentralization project. The interview was conducted during the period (2017-2018), as business representatives were rather inactive in the anonymous interview conducted on specialized online investment forums and congresses.Statistical processing of the obtained results is carried out using generally accepted statistical methods.Results. The estimation of the project prospects implementation is given with consideration of the current trends of the investment businessConclusions. The results of the study showed that in accordance with the views of the interviewed investment business representatives, most of them do not know about the existing management problems in the Ukraine PAS, but, basically, the IBR are ready to invest in cooperation with the PAS, under the conditions of decentralization management model implementation, ready to invest from 100 to 500 thousand hryvnias. (the specified level of investment is related to the fact that the IBR is more willing to remain observers and not risk investing to the PAS, looking for more reliable investment projects).